The COVID-19 pandemic in Portugal: Evolution, Vaccination and Pharmacovigilance - Ferreira da Silva, Renato (2022)
The disease caused by the new SARS-CoV-2 virus (COVID-19) was first reported in December 2019 in Wuhan, China, and subsequently it spread throughout the world.On March 2, 2020, the first two cases of COVID-19 were confirmed in Portuguese territory, with the first death to be registered two weeks later, on March 16. Thereafter, a wide and variable set of sanitary measures were applied, as well as the publication of norms and guidelines by the Directorate-General of Health (DGS) and by the National Authority of Medicines and Health Products, I.P. (INFARMED). Later, on December 27, 2020, the first vaccine against COVID-19 (Comirnaty®; BioNTech Manufacturing GmbH/Pfizer) was administered at the University Hospital Centre of São João, in Porto, marking the beginning of the defined vaccination plan by the task-force and the involvement of different health professionals.Pharmacovigilance of vaccines against COVID-19 is an area of ​​enormous importance, through the generation of real-world evidence on post-marketing safety and effectiveness. The Pharmacovigilance Systems are responsible for receiving, validating, analysing, requesting additional data, codifying and collaborating in the attribution of causality to all suspected adverse reactions.The aim of this article is to portray the COVID-19 pandemic in Portugal, with regard to its evolution, vaccination plan and Pharmacovigilance activities. Additionally, the issue is articulated with the international reality, highlighting the main measures, stakeholders and impact on public health.